2014
DOI: 10.1186/1472-6947-14-54
|View full text |Cite
|
Sign up to set email alerts
|

Staff experiences within the implementation of computer-based nursing records in residential aged care facilities: a systematic review and synthesis of qualitative research

Abstract: BackgroundSince the introduction of electronic nursing documentation systems, its implementation in recent years has increased rapidly in Germany. The objectives of such systems are to save time, to improve information handling and to improve quality. To integrate IT in the daily working processes, the employee is the pivotal element. Therefore it is important to understand nurses’ experience with IT implementation. At present the literature shows a lack of understanding exploring staff experiences within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 35 publications
2
63
0
3
Order By: Relevance
“…Effects of these ICTs on documentation time were mixed within and across the reviews: six reviews demonstrated positive effects [15,16,47,53,56,60], six demonstrated negative effects [15,16,43,47,53,60], and three demonstrated no effect [43,47,60]. Negative results showed that nurses spent more time documenting when they used management systems and the positive results showed the contrary: documentation time diminished with ICTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of these ICTs on documentation time were mixed within and across the reviews: six reviews demonstrated positive effects [15,16,47,53,56,60], six demonstrated negative effects [15,16,43,47,53,60], and three demonstrated no effect [43,47,60]. Negative results showed that nurses spent more time documenting when they used management systems and the positive results showed the contrary: documentation time diminished with ICTs.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, due to some features of CDSSs and management systems (eg, readability of data, remote accessibility of data, better quality of patients’ records, presence of reminders, or automatic alerts), these ICTs supported clinical judgment and decision-making [43,56]. Conversely, some features of the ICTs not previously available on paper, such as copy and paste, drop-down menus, and check boxes, affected the nurses’ capacity to employ critical thinking regarding their patients [60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoitotietojen tulee olla virheettömiä ja täydellisiä, sillä tiedon laatu on edellytys potilaan hyvälle hoidolle [7,8]. Sähköinen potilaskertomus koostuu eritasoisista hierarkkisista tietokokonaisuuksista, joita jäsennetään näkymien, hoitoprosessien vaiheiden ja otsikoiden avulla sekä käytetään kirjaamiseen tarkoitettuja luokituksia ja koodistoja [3].…”
Section: Hoitotiedot Osana Potilaan Hoitoaunclassified
“…16,19,20 Furthermore, a previous systematic review of six studies exploring staff experiences with IT implementation in nursing homes found that the introduction of IT for documentation purposes may bring both benefits and burdens. 21 Consequently, there have been calls to expand research to further examine the impact that electronic documentation systems have on working practices in nursing homes. 9,15,22 Therefore, this literature review aims to add to existing knowledge in the field by exploring the impact of electronic documentation systems on the provision of care in nursing homes.…”
Section: Introductionmentioning
confidence: 99%